Pengenalan Alat Peraga Matematika di SD Negeri Cibubur 01 Pagi Jakarta Timur - Lasia Agustina (Universitas Indraprasta PGRI, 2016)
The aim of this research was to introducing mathematics tool to the learners at the elementary level, especially the fifth grade of State Elementary School Cibubur 01 Pagi. This research was conducted in State Elementary School Cibubur 01 Pagi. From observation during the activity, the learnenrs enthusiastically followed the steps provided. By doing a presentation about introducing tool, and also explained the various benefits of that tool. In addition, at the end of the step, an evaluation that aims to measure students understanding of what has been presented to the learner. The learners have high curiousity. Enthusiasm in following the presentation, ask and answer actively was shown by the learners, giving the feedback that the better tool in learning process gives the more benefits than learning theoretically and without adequate tool.